2020
DOI: 10.1093/heapro/daaa050
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of health education interventions at Dutch music schools

Abstract: A randomized controlled trial was conducted comparing the effects of a biopsychosocial course (PRESTO-Play) vs. physical activity promotion (PRESTO-Fit) to reduce disability related to musculoskeletal disorders in music students. The current study provides an external validation and a formative and process evaluation, allowing for a better interpretation of results. First, a group of experts was asked to complete a structured evaluation of design and content of the trial. Second, quantitative and qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…38 A more specific form is the healthy settings approach, which is ‘concerned to embed health within the culture, ethos, structures and routine life of settings’, 39 and seems particularly pertinent for impacting workplace and university/school culture. Numerous recent studies concluded that there is a need for health promotion and/or healthy settings approaches in school, university and professional-level musicians, 5,16,17,22,34,40 and all our results support this conclusion.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…38 A more specific form is the healthy settings approach, which is ‘concerned to embed health within the culture, ethos, structures and routine life of settings’, 39 and seems particularly pertinent for impacting workplace and university/school culture. Numerous recent studies concluded that there is a need for health promotion and/or healthy settings approaches in school, university and professional-level musicians, 5,16,17,22,34,40 and all our results support this conclusion.…”
Section: Discussionsupporting
confidence: 88%
“…In the only one other than ours where musicians (conservatory students) had already tried a preliminary program, one of the three main determinants, along with institutional support and communication, was student’s motivation. 22 Indeed, end user’s motivation, regardless of population, is considered critical for behaviour change and positive implementation outcomes. 20,26 Although motivation emerged only as a secondary theme in our results, a strong connection between Intervention Characteristics and determinants such as social influences , self-efficacy and motivation became apparent from our data; our participants spoke of the importance of frequent supervision, group activities and short exercise sessions, among other intervention characteristics, to optimise these determinants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Music students at this age are able to assume personal responsibilities for changing their behaviors and choices [ 13 ]. Unfortunately, MP prevention behaviors are less common among music students [ 14 , 15 ], and there is a rising demand for educating them to take care of their own health and adopt proper postures during music practices [ 14 ]. According to Salonen (2018), there is a need to develop more prevention programs to promote health and well-being in music students [ 16 ].…”
Section: Introductionmentioning
confidence: 99%